Klasifikasi Lirik Lagu Bertema Lingkungan dengan Metode Naive Bayes - Putu Ode Irfan Ardika; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Awareness of the importance of protecting the environment is becoming increasingly important in this modern era. Humans as inhabitants of the earth have a responsibility to protect and maintain the natural environment, they live in. Songs can be one of the important roles that can help awaken people to start protecting the environment they live in. This research makes it easy to find songs that have the theme of protecting the environment by classifying song lyrics. This research will create a system that can classify environment-themed song lyrics using the Naive Bayes method with a Multinomial model. The results of the Naïve Bayes test with the Multinomial model get the best results on the composition of the training data and test data of 10.90 which produces a recall score of 38%, precision of 90.4%, F1 score of 53.5%, while for accuracy it gets the best score on the composition of 90:10 with a yield of 75%